Problem Posing to Develop Students' Mathematical Creativity - Hendrajaya, Hendrajaya; Sugiatno, Sugiatno; Suratman, Dede; Rif’at, Mohamad; Putra, Fredi Ganda (Universitas Sarjanawiyata Tamansiswa, 2022)
Student creativity in the process of learning mathematics is very necessary. The low ability to think creatively will greatly affect the overall learning outcomes. One alternative learning that can be used is the problem posing approach. This study aims to determine whether the Problem Posing approach has an effect on students' mathematical creativity. Quantitative research methods with data analysis techniques using the F test are used in this study. The essay test instrument was used to collect data on students' creative thinking abilities. The results showed an increase in students' mathematical creativity after using the Problem Posing approach. The results showed that the effect of the Problem Posing approach on mathematical creativity was 40.49%, this is in the high category. Based on these results, the problem posing approach can be an alternative for teachers in increasing the creativity of students who are still low.